Transpolitan: Development Strategy For The Pearl Transmigration Area - Sudarsono, Faizaldi Ichsan; Dwimawanti, Ida Hayu; Fauziah, Luluk (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to identify transmigration area development plans, analyze transmigration area development models, and analyze transmigration area development strategies that are effectively implemented in the Mutiara Area of Muna Regency so that they are sustainable. This study uses a qualitative research approach, which is carried out with a combination of literature studies and secondary data collection. This study uses a qualitative descriptive research method, which provides a description that is descriptive in nature and is explained deductively. The analysis technique used in this study uses data analysis techniques (content analysis) and SWOT analysis. From the results of this analysis, several recommendations can be made, namely the need to determine the Mutiara transmigration area in Muna Regency, which will become the basis for the development of transmigration areas in the Muna Regency area. In addition to responding to existing problems, it is necessary to design a grand design for the development of transmigration areas and periodic development plans for the implementation of transmigration area development strategies in the Muna Regency area. The ideal solution to minimize problems in the future development of transmigration areas is Green Transpolitan, which puts forward the Pentahelix partnership concept, which has been developed into a model for transmigration area development. Identification and formulation of strategies for the development of transmigration areas in the Mutiara Area of Muna Regency were carried out using a SWOT analysis, which was explained in the findings.